The Problems of English Speaking of Grade 12 Students at Paktha Secondary School in Laos - Keomany, Bounpan; Kanokkamalade , Veerakarrn; Klinchan, Nilratana (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
The purposes of this research were 1) to study the problems of English speaking; 2) to analyze the problems of English speaking; 3) to propose the ways to solve the problems of English speaking of grade 12 students at Paktha Secondary School in Laos. This research used a mixed method combining both quantitative and qualitative data to answer the research questions, the study was based on the analysis of 30 questionnaires, which were distributed to 104 students of grade 12, to know the problems of English speaking and to suggest them the best ways to improve English speaking. In addition, 5 key informant teachers were interviewed to observe vividly their experiences in teaching English as second language. The finding of the problems in this study shows that the most of students faced the difficulties in English speaking in a very short period, lack of vocabulary and lose confidence to speak with another, which were totaled rate at high level (Mean = 4.07, S.D. = 0.68). The finding of the ways to solve the problems show that many respondents required to make self-motivation and to use various strategies to support them on learning English speaking such as; reading more English books, listening to English music, watching English movies, practicing with friends, teachers and other people, which were totaled rate at high level (Mean = 4.38, S.D. = 0.50) According to the in-depth interview, most of the teachers reported that students were lacked of confidence, lacked of skills in learning languages and the ways to solve the problems were to make confidence, motivation and practice more and more in the daily live.